Right Inguinal Obstructed Littre's Hernia in a Child - Rattan, Kamal Nain; Bansal, Shruti; Arora, Ishani; Dhamija, Aastha; Tanwar, Manpreet (Journal of Nepal Paediatric Society, 2017)
Littre’s hernia, in which the hernia sac contains a Meckel’s diverticulum, is extremely uncommon in paediatric population. We are reporting a case of Littre hernia in a 4.5 year old male child who presented with an irreducible mass in right inguinal region. The diagnosis was made peroperatively. The patient was successfully managed by diverticulectomy and herniotomy and is doing well in follow up. J Nepal Paediatr Soc 2016;36(3):300-302